1984
DOI: 10.1515/cclm.1984.22.6.419
|View full text |Cite
|
Sign up to set email alerts
|

Further Evaluation of the SG Test Strip for Estimation of Urinary Osmolality

Abstract: The mass densities of 2000 urines from children and 2000 urines from adults were determined with the new test strip, Multistix SG, and the results were compared with osmolality measurements. Normal urinary Parameters were investigated for possible interference with the test strip reading. Variations in the pH and ionic composition of urine considerably influenced the test strip reading, whereas nonionic compounds, such äs glucose and urea, showed practically no interference. For patients on a normal diet and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
2

Year Published

1988
1988
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 3 publications
1
11
0
2
Order By: Relevance
“…Furthermore, for the same total ionic concentration, different ions influence the SG reading by variable magnitude. These effects were well demonstrated in an experimental study [13]. In urine specimens with constant osmolality, cations like NH 4 2+ , Ca 2+ and Mg 2+ increased the SG reading disproportionately in comparison to Na + and K + .…”
Section: Influence Of Normal Urinary Constituents On Sg Measurementsupporting
confidence: 59%
See 3 more Smart Citations
“…Furthermore, for the same total ionic concentration, different ions influence the SG reading by variable magnitude. These effects were well demonstrated in an experimental study [13]. In urine specimens with constant osmolality, cations like NH 4 2+ , Ca 2+ and Mg 2+ increased the SG reading disproportionately in comparison to Na + and K + .…”
Section: Influence Of Normal Urinary Constituents On Sg Measurementsupporting
confidence: 59%
“…Among the anions, a similar enhancing effect was seen with phosphates and citrate in comparison to chloride, while acetate, lactate, urate, oxalate and sulfate caused no deviation. In the same study ketone bodies were reported to decrease the reagent strip SG reading [13].…”
Section: Influence Of Normal Urinary Constituents On Sg Measurementmentioning
confidence: 80%
See 2 more Smart Citations
“…However, in clinical practice, urine pH is often acidic, especially in the setting of acute kidney injury. USG has not been shown to correlate well with osmolality when urine is acidic in reagent strip testing (6,7), whereas there is no effect of pH on refractometry (5).…”
Section: Introductionmentioning
confidence: 96%